Temporal relation between top-down and bottom-up processing in lexical tone perception - Shuai, Lan; Gong, Tao (Frontiers in Behavioral Neuroscience, 2014)
Speech perception entails both top-down processing that relies primarily on language experience and bottom-up processing that depends mainly on instant auditory input. Previous models of speech perception often claim that bottom-up processing occurs in an early time window, whereas top-down processing takes place in a late time window after stimulus onset. In this paper, we evaluated the temporal relation of both types of processing in lexical tone perception. We conducted a series of event-related potential (ERP) experiments that recruited Mandarin participants and adopted three popular experimental paradigms, namely dichotic listening, lexical decision with phonological priming, and sentence comprehension with semantic violation. By systematically analyzing the lateralization patterns of the early and late ERP components that are observed in these experiments, we discovered that: auditory processing of pitch variations in tones, as a bottom-up effect, elicited greater right hemisphere activation; in contrast, linguistic processing of lexical tones, as a top-down effect, elicited greater left hemisphere activation. We also found that both types of processing co-occurred in both the early (around 200 ms) and late (around 300-500 ms) time windows, which supported a parallel model of lexical tone perception. Unlike the previous view that language processing is special and performed by dedicated neural circuitry, our study have elucidated that language processing can be decomposed into general cognitive functions (e.g., sensory and memory) and share neural resources with these functions.